ANALYSIS OF MEDICATION COMPLIANCE WITH TYPE 2 DIABETES MELLITUS PATIENTS OGAN ILIR DISTRICT 2024 - Widiawati; Ali Harokan; Akhmad Dwi Priyatno (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Diabetes mellitus is a disease that can cause complications if proper treatment is not given. There are still high cases of diabetes mellitus, where there is an increase in diabetes mellitus cases from year to year. This study aims to determine factors related to medication adherence in diabetes mellitus patients at the Pegayut Community Health Center, Ogan Ilir Regency in 2024. The design of this research is quantitative with a cross-sectional approach.4 . The population in this study was 710 diabetes mellitus patients who visited the Community Health Center in 2023, with a total sample of 88 people in this study. The sampling method uses purposive sampling. This research was carried out on 10-29 February 2024. Data collection techniques are interviews using questionnaires. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The results of the research show that there is a relationship between motivation (p value 0.01) and the role of officers (p value 0.03) on compliance with taking medication for diabetes mellitus patients at the Pegayut Community Health Center, Ogan Ilir Regency in 2024. There is no relationship between age (p value 0.82 ), gender (p value 0.88), knowledge (p value 0.68) and family support (p value 0.15) on medication adherence for diabetes mellitus patients at the Pegayut Community Health Center, Ogan Ilir Regency in 2024. The most dominant factors with compliance with taking medication for diabetes mellitus patients at the Pegayut Community Health Center, Ogan Ilir Regency in 2024, namely motivation (p value 0.01) (odds ratio 3.07), meaning that if motivation is sufficient, they are 3.07 times less likely to comply with medication compared to those with good motivation. The conclusion is that there is a relationship between motivation and the role of officers. There is no relationship between age, type, knowledge and family support on compliance with taking medication for diabetes mellitus patients at the Pegayut Community Health Center, Ogan Ilir Regency in 2024. It is hoped that the Community Health Center will continue to provide motivation and support to diabetes mellitus sufferers to comply with taking diabetes mellitus medication and increase their participation. patients through a chronic disease management program (prolanis).